Dysaethria illotata ... - Beljaev, Еvgeniy A.; Titova, Olga L. (Zenodo, 2023)
Dysaethria illotata (Christoph) (Fig. 2) Material examined. 1 ♀, S Kholmsk, 06.VII.2022. Distribution. Russia (S RFE: S * Sakhalin, S Kurils— * Kunashir, Jewish Autonomous Oblast, Primorskii Krai), Japan (Hokkaido, Honshu, Shikoku). Remarks. The specimen from Kunashir, referred as “ Dysaethria moza (Butler) ” by Dubatolov et al. (1994: 19, a female collected on 16.VII.1989), actually is misidentification of D. illotata, judging from the photo of this specimen on the website of Siberian Zoological Museum (Dubatolov 2022a). In the same site on another page, the same photo is posted as “ Dysaethria cretacea (Butler) ” (Dubatolov 2022b), what led to an erroneous indication of D. cretacea for the Kuril Islands (Sinev 2008: 189; Beljaev 2016: 517; Sinev 2019: 234; Sinev 2021; Zolotuhin & Nedoshivina 2021: 348). Thus, here D. illotata is first reported from the Kuril Islands, and D. cretacea is excluded from the fauna of Russia. These findings of D. illotata in Sakhalin and the Kurils significantly expand its ... : Published as part of Beljaev, Еvgeniy A. & Titova, Olga L., 2023, New data on geometroid moths (Lepidoptera: Geometroidea: Uraniidae and Geometridae) from Sakhalin and Moneron islands with notes on their taxonomy distribution and ecology, pp. 1-41 in Zootaxa 5369 (1) on pages 5-6, DOI: 10.11646/zootaxa.5369.1.1, http://zenodo.org/record/10147411 ...